Forecasting Cell Phone Ownership among Children with TurkStat Micro Data: Comparative Performance of Machine Learning Models - Eşidir, Kamil Abdullah (Ahmet Arif EREN, 2025)
In this study, we estimate children's mobile phone ownership and analyze the factors affecting mobile phone ownership among children using the micro data set of the Turkey Child Survey for 2022. RandomForest, XGBoost, Gradient Boosting, and Support Vector Machines (SVM) machine models are used in forecasting. The performance of the models was evaluated with Precision, Recall, F1 Score and ROC AUC metrics. The findings show that children's age and access to the internet have a significant impact on cell phone ownership. Machine learning models provided high accuracy values in terms of statistical metrics. The study found that machine learning models improve decision-making processes and provide effective tools for policymakers. Simultaneously, it has been demonstrated that they can be effectively utilized in the field of social sciences. The high accuracy rates achieved by the models demonstrate that data-driven policy development processes can be enhanced to become more effective and efficient.

Bu çalışmada, 2022 yılı Türkiye Çocuk Araştırması mikro veri seti kullanılarak çocukların cep telefonu sahipliğini tahmin edilmiş ve çocuklarda cep telefonu sahipliğini etkileyen faktörler analiz edilmiştir. Tahminlemede RandomForest, XGBoost, Gradient Boosting ve SVM makine öğrenme modelleri kullanılmıştır. Modellerin performansı Kesinlik, Duyarlılık, F1 Skoru ve ROC AUC metrikleri ile değerlendirilmiştir. Elde edilen bulgular, çocukların yaşlarının ve internete erişim imkânlarının cep telefonu sahipliği üzerinde belirgin etkisi olduğunu göstermiştir. Makine öğrenimi modelleri, istatistiksel metrikler açısından yüksek doğruluk değerleri sağlamıştır. Çalışma, makine öğrenimi modellerinin karar alma süreçlerini geliştirdiğini ve politika yapıcılar için etkili araçlar sağladığını ortaya koymuştur. Aynı zamanda, makine öğrenimi modellerinin sosyal bilimler alanında etkili bir şekilde kullanılabileceği de gösterilmiştir. Modellerin sunduğu yüksek doğruluk oranları ile veri odaklı politika geliştirme süreçlerinin daha etkin ve verimli hale getirilebileceği anlaşılmıştır.
TÜİK Mikro Verileri ile Çocuklarda Cep Telefonu Sahipliğinin Tahmini: Makine Öğrenimi Modellerinin Karşılaştırmalı Performansı
Keywords: Econometrics (Other); Ekonometri (Diğer); Research; Science and Technology Policy; Araştırma; Bilim ve Teknoloji Politikası; Policy and Administration (Other); Politika ve Yönetim (Diğer)